A complete solution to the infinite Oberwolfach problem. Issue 5 (5th February 2020) - Costa, Simone
Abstract: Let F be a 2‐regular graph of order v . The Oberwolfach problem, OP ( F ), asks for a 2‐factorization of the complete graph on v vertices in which each 2‐factor is isomorphic to F . In this paper, we give a complete solution to the Oberwolfach problem over infinite complete graphs, proving the existence of solutions that are regular under the action of a given involution free group G . We will also consider the same problem in the more general context of graphs F that are spanning subgraphs of an infinite complete graph K and we provide a solution when F is locally finite. Moreover, we characterize the infinite subgraphs L of F such that there exists a solution to OP ( F ) containing a solution to OP ( L ).